Mitigating agency issues in corporates: the potential of artificial intelligence - Suthakar, D. (Faculty of Law, University of Colombo, 2021)
The article explores the effectiveness of artificial intelligence (AI) to reduce the problems pertaining to agent and principal relationships in Corporates. The board of directors has the ultimate responsibility for managing the business and related affairs of the corporation on behalf of such corporations. They accrue more information about the corporation and anticipate acting in good faith. The core problem arises when a director does not act in the company's best interests, for instance The catastrophic fall of Enron in 2011, where the board committed repeated fiduciary failures by allowing Enron to engage in high-risk accounting and interested transactions. It is widely accepted that this high-profile collapse was caused by a failure to avert conflict of interest. This is because the agency problem reached such a substantial proportion that it has led to a collapse of the company. The research argues that AI can be the best tool to assist the directors in exercising the duty of care, loyalty and business judgments to fulfil their fiduciary duties Consequently, the research article addresses the central question - Are existing Sri Lanka laws sufficient to enable directors to use AI to assist when fulfilling their responsibilities to benefit companies? To this end, the paper examines the potentials of AI to mitigate the agency problems that arise between the directors and the company. The study is basically a doctrinal analysis, and essential data are collected from primary and secondary sources, including statutes and case laws, and concludes that the existing corporate principles of Sri Lanka is to be amended with a new set of principles and laws for the use of the intra- firm AI to mitigate such agency issues. Such principles shall comply with the best standard, for instance as the best practices for AI recommended in recent European Parliament resolution.
Keywords: agency problem; artificial intelligence; conflict of interest; corporate management; directors